A new model towards sustainable socio-economic development using the principles of bioregionalism, illustrated through a case study in SW Botswana - Wiersma, Erica Ingrid (School of Architecture, Planning and Geomatics, 2016)
According to Brunkhorst (2001) and Raeberg (1997), governments who are responsible for regional (territorial) planning are in effect planning blindly as they are not taking into account the brilliant work done in related fields which could change their attitude towards planning, design, ecology & technology. The global debates on scarce resources and climate change which are causing governments to have to take a stand, pose questions such as: How are Scarce Resources Managed? How will injustices to the poor be rectified? What policies and guidelines are in place to promote sustainability? The theory is out there, but little or no practical implementation of the theory at broad scale through fine scale has been done to date. To this end I have created a model which takes into consideration these global issues, and tested it on the SW Wildlife ecosystem of Botswana which has all the characteristics mentioned above. Lessons have been learned from failures in Implementation Strategies at Gudigwe (N Botswana) where insufficient planning for the needs and capabilities of the local villagers created a mismatch of the socio-economic product created and the outcomes anticipated. Another example of failure was the unanticipated social culture of the Baswara who take care of each other above the needs of outsiders. The guests and management were at odds with the staff due to these cultural differences at Mababe Village Sankuyo Trust, NW Botswana. The study will contribute a model of bioregional planning from broad to fine scale which can be used in the planning & design of such regions in the future. The macro biogeographic region is defined at the Broad Scale and at the Fine Scale appropriate socioeconomic sustainable interventions are detailed.